Climatic conditions of wind energy use in the Polonyna Borzhava Mountains (Transcarpathia, Ukraine) - Hadnagy Istvan; Hadnagy István; Гаднадь Іштван; Tar Károly; Lázár István; Kohut Erzsebet; Kohut Erzsébet; Когут Ержебет (Genesis Sustainable Future Ltd., 2020)
Abstract. This paper deals with the statistical structure, seasonal peculiarities of wind climate at meteorological station Play (in Ukrainian: метеорологічна станція Плай, location: 48°40'1'' N; 23°11'51'' E, 1330 m above sea level) located in the Polonyna Borzhava Mountain of the North-Eastern Carpathians. Furthermore, it determines significant parameters of exploiting wind energy. Weibull distribution was applied to determine specific wind power and characterize its annual course. Wind speed was analyzed together with the available daily and yearly course of wind power. Wind power density determined by means of distribution parameters at Play is 169.0 W/m2 and 8.0-9.0 m/s winds yield most energy over the year. The minimum number of energetically utilizable wind hours is in summer, while its maximum is in spring. On the territory represented by the measuring point, a 3 m/s start-up speed wind turbine could operate 63% time over the year. Finally, the periods were specified, and those wind directions were chosen that are richer in wind energy than others. The most frequent characteristic wind direction with the highest mean velocity in each season is southwestern; its average relative frequency is 34.4%. Mean speed of characteristic wind directions is 5.8 m/s. South-western wind direction yields 47% of the total energy.
Keywords: wind energy; wind speed; wind direction; wind power density; Weibull distribution; Transcarpathia